Pendampingan Implementasi Rekam Medis Elektronik Berbasis SNARS Dalam Mendukung Akreditasi KARS Dan Peningkatan Mutu Pelayanan Rumah Sakit - Diah Karlina (STIKES Columbia Asia Medan, 2026)
The digital transformation of healthcare requires hospitals to optimally implement Electronic Medical Records (EMR) in accordance with the National Hospital Accreditation Standards (SNARS). However, challenges remain related to human resource readiness and the effective use of EMR to support KARS accreditation and service quality improvement. This community service activity aimed to provide assistance in implementing SNARS-based EMR at Mitra Sejati General Hospital, Medan. A descriptive–qualitative approach was applied through education, structured training, focused group discussions, and peer group mentoring involving healthcare professionals and supporting staff. The results demonstrated an improvement in participants’ understanding of SNARS, increased compliance of EMR implementation with KARS standards, and enhanced quality and traceability of medical record documentation. The assistance also improved hospital readiness for accreditation and contributed to quality and patient safety improvement. It can be concluded that SNARS-based EMR implementation assistance is an effective strategy to support KARS accreditation and enhance hospital service quality.